Osteopoikilosis: Rare case with incidental radiographic findings - Azarfar, Azin; Taj, Hiffsa; Seifert, Michael (International Journal of Medicine, 2020)
We report a case of benign, autosomal dominant, sclerosing dysplasia of bone in a 41-year-old man. This is a very rare disorder character-ized by numerous, symmetric, homogenous bone islands. The disease is mainly asymptomatic and requires no treatment.Â Â